Takayasu Arteritis in Pregnancy (London Journal of Medical and Health Research, 2023)
Takayasu arteritis is a rare type of vasculitis, a group of disorder that causes large vessel inflammation. The disease can lead to narrowed or blocked arteries, or to aneurysm and tear. It may lead to complications like high blood pressure, heart failure, stroke, transient is cheamic attack and aneurysm in aorta. A healthy pregnancy is possible with the disease but it is a medical challenge. It usually complicates the latter half of the pregnancy and causes hypertension, organ dysfunction and feotal growth restriction. Pregnancy with TA is a medical challenge as the results of American college of rheumatology highlights the serious concerns ie miscarriage rate of 11% and intrauterine death of 1%, preterm delivery rate was 15%, 16% of pregnancies had IUGR and 28% of patients required delivery by LSCS (ACR). Here presenting a case of G4P3IUFD3 with previous 1 LSCS with Takayasu arteritis with chronic hypertension with late onset severe IUGR. Following a multidisciplinary approach, she delivered a live born female child with low birth weight. Her postpartum course remained uneventful. Despite advancements in cardiovascular management and new drugs, the optimal management for pregnant patients with this disease remains elusive.